Language Acquisition and Language Development of Children - Nadia Raifah Nawa Kartika; Kartika s (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2019)
General Psycholinguistics is the study of how the observation or perception adults of the language and how it produces language also regarding underlying cognitive processes when a person uses language. This article focused on language acquisition and language development of children. There is problem that faced in language teaching Psycholinguistics. As psycholinguistics is a core of language, knowing the language acquisition and language development of children is one of solutions to solve the problems in language teaching. It is divided two kinds of languages, Language Acquisition of Children and Language Development of Children.